2019
DOI: 10.3171/2018.7.spine18657
|View full text |Cite
|
Sign up to set email alerts
|

Artificial disc replacement versus fusion in patients with cervical degenerative disc disease with radiculopathy: 5-year outcomes from the National Swedish Spine Register

Abstract: OBJECTIVEThe long-term efficacy of artificial disc replacement (ADR) surgery compared with fusion after decompression for the treatment of cervical degenerative disc disease and radiculopathy has not previously been investigated in a population-based setting.METHODSAll patients with cervical degenerative disc disease and radiculopathy who were in the national Swedish Spine Registry (Swespine) beginning in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…30 Posterior foraminotomy preserves motion at the index level, but no protection against deterioration at the adjacent cervical segments has been realized in practice. 13,17 Posterior foraminotomy surgery decreased in the US from 3.4/100,000 in 1992 to 1.2/100,000 in 2005. 27 The national Swedish Spine Register (Swespine) was founded in 1993.…”
mentioning
confidence: 99%
“…30 Posterior foraminotomy preserves motion at the index level, but no protection against deterioration at the adjacent cervical segments has been realized in practice. 13,17 Posterior foraminotomy surgery decreased in the US from 3.4/100,000 in 1992 to 1.2/100,000 in 2005. 27 The national Swedish Spine Register (Swespine) was founded in 1993.…”
mentioning
confidence: 99%
“…However, they performed combined analysis using Bryan and Prestige artificial discs and found significant differences in symptomatic ASD requiring surgery as early as after 7 years 40 . Surprisingly, MacDowall et al 51 conducted a retrospective study based on a Swedish database and found that CDA had a similar secondary surgery rate at the adjacent level but a higher secondary surgery rate at the index level with significant difference. However, based on our long-term results, CDA had a significantly lower rate of total secondary surgery, secondary surgery at the adjacent level, and secondary surgery at the index level, which is consistent with mid-term to long-term results 17 However, this finding is contrary to the short-term to mid-term result reported by Zhang et al 52 that the secondary surgery rate at the adjacent level showed no significant difference.…”
Section: Discussionmentioning
confidence: 98%
“…However, they performed combined analysis using Bryan and Prestige artificial discs and found significant differences in symptomatic ASD requiring surgery as early as after 7 years. Surprisingly, MacDowall et al . conducted a retrospective study based on a Swedish database and found that CDA had a similar secondary surgery rate at the adjacent level but a higher secondary surgery rate at the index level with significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the treatment of CSM, anterior cervical surgery has been widely accepted for some patients [ 7 , 8 ]. Nevertheless, with the increasing application of these surgeries, deficiencies and complications related to these procedures have been reported [ 9 ].…”
Section: Introductionmentioning
confidence: 99%